Human resource needs and costs for nurse-led HIV pre-exposure prophylaxis provision in primary care in Eswatini and opportunities for task sharing [research data] - Kohler, Stefan; Dalal, Shona; Hettema, Anita; Matse, Sindy; Bärnighausen, Till; Paul, Nicolas (Universität, 2024)
Background: The global expansion of HIV pre-exposure prophylaxis (PrEP) includes health systems that face a shortage of skilled health care workers (HCWs). We estimated the human resource needs and costs for providing PrEP in nurse-led primary care clinics in Eswatini. Furthermore, we assessed potential cost savings from task sharing between nurses and other HCW cadres. Methods: We conducted a time-and-motion and costing study in a PrEP demonstration project between August 2017 and January 2019. A form for recording time and performed activities (“motion”) was filled by HCWs of six primary care clinics. To estimate the human resource needs for specific PrEP activities, we allocated recorded times to performed PrEP activities using linear regression with and without adjusting for a workflow interruption, that is, if a client was seen by different HCWs or by the same HCW at different times. We assessed a base case in which a nurse provides all PrEP activities and five task shifting scenarios, of which four include workflow interruptions due to task sharing between different HCW cadres. Results: On average, PrEP initiation required 29 min (95% CI 25-32) of HCW time and PrEP follow-up 16 min (95% CI 14-18). The HCW time cost $4.55 (uncertainty interval [UI] 1.52-9.69) for PrEP initiation and $2.54 (UI 1.07-4.64) for PrEP follow-up when all activities were performed by a nurse. Time costs were $2.30-4.25 (UI 0.62-9.19) for PrEP initiation and $1.06-2.60 (UI 0.30-5.44) for PrEP follow-up when nurses shared tasks with HCWs from lower cadres. Interruptions of the workflow added, on average, 3.4 min (95% CI 0.69-6.0) to the time HCWs needed for a given number of PrEP activities. The cost of an interrupted workflow was estimated at $0.048-0.87 (UI 0.0098-1.63) depending on whose time need increased. Conclusions: A global shortage of skilled HCWs could slow the expansion of PrEP. Task shifting to lower-cadre HCW in nurse-led PrEP provision can free up nurse time and reduce the cost of PrEP provision even if interruptions associated with task sharing increase the overall human resource need.
Gefördert durch: World Health Organization: H9/181/R; U.S. Agency for International Development: U.S. President’s Emergency Plan for AIDS Relief
Gesehen am 29.05.2024
Keywords: Forschungsdaten; Datenbank